PELAKSANAAN REFORMASI BIROKRASI PADA PELAYANAN PAJAKELECTRONIC E-FILLING SYSTEM DI KANTOR PELAYANAN PAJAK PRATAMAPEKANBARU TAMPAN 2018 - Andre Nal Saputra; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study is motivated by the problem of bureaucratic reform in the Tax Service Electronic e-filling system in the ease, speed, and accuracy in providing services in the taxation sector, as a concrete step to improve service quality at the Pekanbaru Tampan Tax Service Office to report tax payments using E-filling system. The purpose of this study is to find out how the bureaucratic reform of Tax Reporting Services electronically at the Pekanbaru Tampan Primary Tax Service Office and the efforts made by the Primary Tax Office in increasing public interest in using the E-filling system. The theoretical concept used by researchers is the Governence Bureaucracy Reform which has determinative indicators, namely Infrastructure, Communication, Level of Connectivity and Use of IT by the Government, Readiness of Human Resources in the Government, Availability of Funds and Budgets, Legal Devices, Changes in Pradigma. This study uses qualitative research methods, with descriptive data review. In collecting data, researchers used interview, observation, documentation, and literature study techniques. The results of this study indicate that bureaucratic reform of tax services using the E-filling system conducted at the Pekanbaru Tampan Primary Tax Service Office has been said to be quite good. Carried out by the tax service office in increasing public interest in the use of the E-flling system is the first readiness of human resources, namely the lack of employees in the Pekanbaru Primary Tax Service Office. The second is the availability of budget funds that are used as costs to improve employee performance such as procurement of funds related to budget and policy allocations, the third is the legal instruments used, such as laws and regulations, as well as regional regulations, and the fourth is the change of paradigm, which is an agency's desire in improving its performance in order to improve better and quality services for the future. Keywords:Bureaucratic Reform of Tax Services in Tax reporting